Deep fathom - Rollins, James, 1961- (Harper, 2010)
As solar flares and earthquakes wreak havoc upon the Earth, Air Force One and America's president vanish and ex-Navy SEAL Jack Kirkland must embark on a perilous mission below the ocean's surface to save the world from destruction.